Exploring the causes of elevated kinesiophobia in post-coronary stenting patients: a qualitative analysis in a cardiac rehabilitation setting - Ying Zhang; Rui Xu; Junfang Miao; Junxia Miao; Weizhao Wang; Mengmeng Dong; Fangli Li (BMJ Open)
Objectives The primary aim of this study is to investigate the factors contributing to the development of kinesiophobia in patients following coronary artery stent implantation, integrating perspectives from both patients and healthcare professionals. The main hypothesis is that understanding and methods for effectively overcoming the fear of exercise and improving the effectiveness of cardiac rehabilitation require further exploration from both patient and professional viewpoints.Design This qualitative study used a semi-structured interview approach to gather data from participants.Setting The study was conducted at a hospital in Gansu province, China, focusing on the level of care provided to cardiac rehabilitation patients.Participants A total of 11 cardiac rehabilitation patients identified as having kinesiophobia (Tampa Scale for kinesiophobia Heart, TSK-SV Heart >37) through screening and nine healthcare professionals participated in the study. The selection criteria included patients undergoing cardiac rehabilitation and professionals involved in their care.Results The study identified a core theme, ‘Navigating Fear and Uncertainty’, encompassing five themes that elucidate how various factors contribute to the prevalent phenomenon of kinesiophobia among patients. These were further delineated into 11 subthemes: (1) physiological factors (fatigue, negative illness experiences), (2) psychological factors (hypervigilance, psychogenic anxiety and depression), (3) capacity factors (reduced physical abilities, lack of rehabilitation knowledge and skills), (4) motivational factors (low exercise self-efficacy, rehabilitation cognitive errors) and (5) support systems (primary caregivers, healthcare professionals and medical support). The results provide a qualitative understanding rather than quantitative measures, hence no CIs or statistical significance levels are provided.Conclusions The kinesiophobia observed in patients following coronary artery stent implantation stems from the combined influence of multiple factors, warranting early assessment and intervention by healthcare professionals. The study suggests that healthcare institutions should address the practical concerns faced by cardiac rehabilitation patients and enhance familial, medical and societal support systems to increase patient engagement and compliance with exercise rehabilitation. Further research is needed to develop and validate interventions based on these findings.